Torque Characteristics Analysis of Slotted-Type Axial-Flux Magnetic Coupler in the Misalignment State - Yutang Qi; Chaojun Yang; Yiwen Zhang; Chao Guo; Amberbir Wondimu Tadesse (Machines)
In this article, a simple and practical magnetic equivalent charge model is proposed to predict the torque of a slotted-type axial-flux magnetic coupler (SAMC) under conditions of radial misalignment, angle misalignment, and synthetic misalignment. The magnetic field generated by the permanent magnet (PM) disk and the induced magnetic field generated by the slotted conductor sheet (CS) are equivalent to the surface magnetic charge, respectively. Particularly, the induced magnetic field produced by eddy current considering skin depth in the conductor sheet is introduced into the magnetic equivalent charge model. Combined with Coulomb’s law of magnetic field, the formulas of torque and axial force are both derived. Using this method, the torques in three cases of misalignment are calculated. Finally, the effectiveness of the model is verified by the finite element method (FEM) and experiment; the results calculated by the magnetic equivalent charge model are basically consistent with those from the finite element method and experiment. The derived formula is suitable for small air gaps, small slip rates, and small radial deflection distances. Additionally, the limitations of the method proposed are discussed, which is of great help for understanding the torque transmission of the magnetic coupler in the misalignment state.